A Novel PKD1 Mutation Associated With Autosomal Dominant Kidney Disease and Cerebral Cavernous Malformation - Thomas, Christian; Zühlsdorf, Andrea; Hörtnagel, Konstanze; Mulahasanovic, Lejla; Grauer, Oliver M.; Kümpers, Philipp; Wiendl, Heinz; Meuth, Sven G. (Frontiers in Neurology, 2018)
Autosomal dominant polycystic kidney disease (ADPKD) is a genetic disorder characterized by the presence of renal cysts and specific extrarenal abnormalities. ADPKD is caused by mutations in either PKD1 or PKD2 genes that encode for integral membrane proteins Polycystin-1 (PC1) & Polycystin-2 (PC2), respectively. Extrarenal involvement includes noncystic manifestations such as dilatation of the aortic root, artery dissection and intracranial aneurysms. Cerebral cavernous malformation (CCM) is a rare vascular malformation disorder characterized by closely clustered and irregularly dilated capillaries that can be asymptomatic or cause variable neurological manifestations, such as seizures, non-specific headaches, progressive or transient focal neurologic deficits, and cerebral hemorrhages. Familial CCM is typically associated with mutations in KRIT1 (CCM1), CCM2, and PDCD10 (CCM3). The co-occurrence of ADPKD and CCM has been previously described in a single patient, although genetic analysis was not performed in this study. We report here a family with ADPKD associated with cerebral cavernous malformation in two sisters. Direct sequencing of the index patient revealed a single novel heterozygous frameshift mutation in PKD1, and lack of mutations in genes usually related to CCM. This suggests that CCM represents an additional phenotype of ADPKD.